Evaluation of nutrient management options for maize-wheat cropping system in Inceptisol - Jajoria, D.K.; Sharma, S.K.; Verma, Arvind; Narolia, G.P. (Annals of Agricultural Research, 2016)
A field experiment was conducted for 4 years (2007-08 to 2010-11) at Instructional Farm of RajasthanÂ College of Agriculture, Udaipur, Rajasthan to study the influence of balanced use of nutrients onÂ yield of maize-wheat cropping system and nutrient status of soil. The experiment was laid-out onÂ sandy clay loam soil by adopting randomized block design which included five treatments viz.Â T1 = Farmers’ practice*, T2 = Recommended dose 90 : 30 : 0 kg NPK for maize and 120 : 60 : 0 NPK forÂ wheat, T3 = 150% recommended dose, T4 = NPK through soil test recommendation (STR**) andÂ T5 = site specific nutrient management (SSNM***). Variety ’PEHM-2’ for maize and ’Raj-4037’ forÂ wheat were taken during Kharif and Rabi seasons, respectively as test crop. The highest yield ofÂ maize and wheat (4.32 and 4.77 t haâ€“1) was obtained in the treatment SSNM followed by 150%Â recommended dose and NPK through soil test recommendation. However, the yields obtained underÂ latter two treatments were statistically at par but superior to the farmers’ practice. Application ofÂ 150% recommended dose resulted in higher residual available NPK as compared to other treatments.Among all the treatments, SSNM recorded higher gross return (` 43753 haâ€“1), netreturn (` 33168 haâ€“1) and B:C ratio (3.13) for maize crop and gross return (` 69552 haâ€“1), net return(` 53047 haâ€“1) and B:C ratio (3.21) for wheat crop. *Farmers’ practice - 80:30:0 kg haâ€“1 N:P:K for maize and 100:45:0 kg N:P:K for wheat **STR - 120:60:30 kg haâ€“1 N:P:K for maize and wheat ***SSNM - 120:60:30:40:5 kg/ha N:P:K:S:Zn for maize and 120:60:30: kg/ha N:P:K for wheat.